Variations in Diameter of the Left Coronary Artery and its Main Branches among Adult Population of Khartoum State, Sudan - Muntaser, Alhassen; Abuzer, Abdalla; Tahir, Ali; Mohamed, Akeel (Journal of Hypertension and Cardiology, 2021)
Themain left coronary artery and its branches have wide variability in its morphology regarding caliber, as seen through angiographic imaging. This study aims to determine the diameters of the left coronary artery and its branches among the Sudanese population & to correlate these diameters and the personal and health data. Angiography of 441 patients of both sexes was used in this study. Personal and health information was obtained from the records. We found that the left coronary artery's diameter was between 2.90- 4.90mm, with an average of 3.96mm. The diameter of the left circumflex artery in the range between 1.70- 4.70mm, with an average of 2.73mm, and that of the anterior descending artery in the range between 1.20- 4.70mm, with an average of 2.78mm. We correlated the diameters of the three arteries and the variables of age, gender, BMI, coronary artery disease, smoking habits, and hypertension. Wefound many correlations to be significant. We concluded that the diameters of the left coronary artery and its branches are affected by age, gender, BMI, coronary artery disease, smoking habits, and hypertension.
Keywords: Left coronary artery; Left circumflex artery; Anterior descending artery Angiography; BMI; Coronary artery disease; Smoking habits; Hypertension.